Numerical simulation on lattice structure construction and optimization method for additive manufacturing. (1st November 2022) - Zhang, Xinju; Cheng, Quntao; Xue, Zhanpu; Ji, Lisong; Kong, Shuangshuang; Ji, Yunguang; Yan, Haipeng; Qian, Songrong
Highlights: The lattice structure construction method based on finite element mesh is proposed. The optimization design method of heterogeneous lattice structure for additive manufacturing based on MIST method is proposed. The lattice structure construction and optimization problem realized by using parametric language APDL. Abstract: With the improvement of lightweight demand and the development of additive manufacturing technology, the manufacturing of complex lattice structure is made possible, and the construction of complex lattice structure is became more and more important. However, the existing commercial software will have the phenomenon of boundary cell damaged when realizing lattice structure for curve and surface graphics. Being aimed at the problem of boundary unit cell damage in the construction of large-scale lattice structure, this paper proposes a lattice structure construction method based on finite element mesh. Through the description of the parameterization, implementation principle and specific process of lattice structure, and finally compared with the existing commercial software inspire, the result is shown that this method is better than the lattice structure construction problem of commercial software, It also is solved the problem of boundary cell damage in the construction of large-scale lattice structure. In addition, many studies show that the optimized heterogeneous lattice structure is had better mechanical performance. In this paper, a method for optimizing the cross-sectional area of lattice members is proposed based on the mist method. In two-dimensional and three-dimensional numerical examples, the total volume strain energy of the lattice structure has been improved by more than 60% in theory.